IMPROVING ENGLISH LISTENING SKILL THROUGH LANGUAGE LABORATORY MEDIA - Feby Akhdiyati (Universitas Galuh, 2018)
The objective of research is to improve English listening ability through the use of the language laboratory at SMA Sandikta. This study used action research methods which involved two cycles. This study was conducted at Sandikta Senior High School XI IPA. School year 2014/2015.The research carried out at the beginning of January to May 2015. Based on the data from the pre test, it shows that the students’ competencies in listening English is still low. After given treatment throughout the cycles (planning, acting, observing, and reflecting)and the result of post tests, the students’ ability in listening English had been improved. Qualitative data analysis shows that the students are interested and enjoyed during the process. The students listen better after the treatment. The results of the analysis is strengthen by quantitative data analysis which shows an increase in listening skills (listening) English. It can be seen from the data of the students, in cycle 1, average value of 60.375 students while in the cycle 2 of the average value of 81.25 students. Therefore, there is improvement in English listening through language laboratory. Keywords: ability, listening, language laboratory